2012
DOI: 10.1103/physrevb.85.045426
|View full text |Cite
|
Sign up to set email alerts
|

Role of structure of C-terminated4H-SiC(0001¯) surface in growth of graphene layers: Transmission electron microscopy and density functional theory studies

Abstract: Principal structural defects in graphene layers, synthesized on a carbon-terminated face, i.e. the SiC(0001 ) face of a 4H-SiC substrate, are investigated using microscopic methods.Results of high-resolution transmission electron microscopy (HRTEM) reveal their atomic arrangement. Mechanism of such defects creation, directly related to the underlying crystallographic structure of the SiC substrate, is elucidated. The connection between the 4H-SiC(0001 ) surface morphology, including the presence of the single … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 54 publications
1
19
0
1
Order By: Relevance
“…The picture is not equally clear for graphene grown on the C face. Apart from a general acceptance of a weaker interface coupling with respect to the Si face [16,17], uncertainty still exists on whether graphene * antonino.lamagna@imm.cnr.it grows directly on the C-terminated surface [18,19] or if it is preceded by either ordered surface reconstructions [16] or a disordered/amorphous interface layer [20][21][22]. Further dispute exists on whether the formation of graphene on the C face is driven by an epitaxial process, as the presence of domains with different orientations and numbers of graphene layers indicates the possible suppression of related mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The picture is not equally clear for graphene grown on the C face. Apart from a general acceptance of a weaker interface coupling with respect to the Si face [16,17], uncertainty still exists on whether graphene * antonino.lamagna@imm.cnr.it grows directly on the C-terminated surface [18,19] or if it is preceded by either ordered surface reconstructions [16] or a disordered/amorphous interface layer [20][21][22]. Further dispute exists on whether the formation of graphene on the C face is driven by an epitaxial process, as the presence of domains with different orientations and numbers of graphene layers indicates the possible suppression of related mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…It can be assumes that a graphene stack grows as a thin film parallel to the local SiC substrate planes and follows the local morphology of the SiC surface, which was already shown in TEM experiments. [20][21][22][23] In the case of the on-axis SiC (0001) substrates, one can expect surface steps originating from substrate etching in a hydrogen atmosphere. 24 We should expect a diffraction pattern composed of SiC scattering and graphene stack scattering but with the graphene scattered intensity many orders of magnitude lower than SiC X-ray reflections (Fig.…”
mentioning
confidence: 99%
“…Firstprinciples calculations has been done to study graphene buffer layer formation on SiC(0001), diffusion of carbon on SiC [6], stability and reactivity of atomic steps of SiC in the initial graphene growth stage [7]. Experimental studies have been done to understand mechanisms of epitaxial graphene growth on SiC(0001) [8], SiC(0001) [9], non-polar SiC surfaces [10] and to elucidate role of carbon diffusion [11] and silicon sublimation [9]. It has been shown that graphene with reduced pit density can be grown on nominally flat SiC substrates [9] and graphene quality can be further improved when grown in high argon pressure [12].…”
Section: Introductionmentioning
confidence: 99%